Salmonella Typhimurium metabolism affects virulence in the host – A mini-review. (May 2018) - Herrero-Fresno, Ana; Olsen, John Elmerdhahl
Abstract: Salmonella enterica remains an important food borne pathogen in all regions of the world with S. Typhimurium as one of the most frequent serovars causing food borne disease. Since the majority of human cases are caused by food of animal origin, there has been a high interest in understanding how S. Typhimurium interacts with the animal host, mostly focusing on factors that allow it to breach host barriers and to manipulate host cells to the benefit of itself. Up to recently, such studies have ignored the metabolic factors that allow the bacteria to multiply in the host, but this is changing rapidly, and we are now beginning to understand that virulence and metabolism in the host are closely linked. The current review highlights which metabolic factors that are essential for Salmonella Typhimurium growth in the intestine, in cultured epithelial and macrophage-like cell lines, at systemic sites during invasive salmonellosis, and during long term asymptomatic colonization of the host. It also points to the limitations in our current knowledge, most notably that most studies have been carried out with few well-characterized laboratory strains, that we do not know how much the in vivo metabolism differs between serotypes, and that most results are based on challenges in the mouse model of infection. It will be very important to realize whether the current understanding of Salmonella metabolism in the host is true for all serotypes and all possible hosts. Highlights: Salmonellosis is the most costly food borne infection. We need to understand what determines the high success of Salmonella. The current review highlights that Salmonella Typhimurium is a versatile bacterium. Its metabolism enables it to grow in different hosts and niches in the host. Understanding in host metabolism may lead to novel ways to prevent infections.